Oxytocin and Autism Spectrum Disorders: A Systematic Review and Meta-Analysis of Randomized Controlled Trials - Ooi, Yoon Phaik; Weng, Shih-Jen; Kossowsky, Joe; Gerger, Heike; Sung, Min (Pharmacopsychiatry, 2017)
Aim: Oxytocin presents an exciting potential to target the core symptoms of autism spectrum disorder (ASD) pharmacologically in an easily administered, cost-effective form with possibly minimal adverse effects. But, there are still major gaps in this area of research. This paper reviewed randomized controlled trials (RCTs) examining the effects of oxytocin administration on social cognition and restricted, repetitive behaviors in individuals with an ASD.Method: Electronic literature searches were conducted from PsycINFO, PubMed, Web of Knowledge, and EMBASE for RCTs published through June 2015.Results: 12 RCTs were included in this review. 7 out of the 11 studies that examined social cognition reported improvements. Additionally, one out of the 4 studies on restricted, repetitive behaviors, reported improvements following oxytocin administration. However, results from our meta-analyses suggest that oxytocin has no significant effect on these 2 domains.Conclusion: Previous evidence revealed mixed findings about the effects of oxytocin on ASD. Given the limited number of RCTs, our summary of findings on the effectiveness of oxytocin on ASD should still be considered tentative.
Keywords: autism spectrum disorders; oxytocin; social cognition; emotion recognition; restricted; repetitive behaviors